Field schools for Kenyan dairy farmers - Minjauw, B.; Muriuki, H.G.; Romney, Dannie L. (2003)
Currently over 1000 Farmer Field Schools (FFS) on integrated pest management (IPM) and/or integrated soil management are being successfully implemented in Kenya and many more in Africa as a whole. In 2001, the DFID/FAO project on Farmer Field Schools for livestock began adapting and testing the FFS methodology for animal health and production, focussing on smallholder dairy farmers. Ten pilot FFS have been established in five different agro-ecological zones in central, Rift Valley and coastal provinces of Kenya. This paper discusses the activities of the FFS, and looks into initiating FFS for livestock.